2006
DOI: 10.1007/s11548-006-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of cranial and craniofacial bone defects with prefabricated individual titanium implants: follow-up and evaluation of 166 patients with 169 titanium implants from 1994 to 2000

Abstract: Objective The TICC (Tomography, Image processing, CAD, CAM) processing chain developed at the RuhrUniversity Bochum in Germany has already been established since several years for the reconstruction of large pre-existing posttraumatic skull defects with individual prefabricated implants made of pure titanium. So far, more than 500 titanium implants have been inserted with great success at more than 60 clinical centres worldwide. The aim of our study was to evaluate all implants inserted between 1994 and 2000. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In a large Australian study with long-term follow-up, not a single patient noted a poor cosmetic result 52 ; multicenter experiences in Europe and the United States also report favorable results. 53 These encouraging outcomes, combined with mechanical strength, low infection rates, and biocompatibility make titanium an attractive option. 54 Titanium is sometimes described as a material of last resort in the adult population.…”
Section: Titaniummentioning
confidence: 99%
“…In a large Australian study with long-term follow-up, not a single patient noted a poor cosmetic result 52 ; multicenter experiences in Europe and the United States also report favorable results. 53 These encouraging outcomes, combined with mechanical strength, low infection rates, and biocompatibility make titanium an attractive option. 54 Titanium is sometimes described as a material of last resort in the adult population.…”
Section: Titaniummentioning
confidence: 99%
“…In 2006, Eufinger et al showed a comparable reoperation rate of 21% and secondary implant removal rate in 8.4% for titanium. 6 The main reasons for explantation were wound dehiscence with infections in 5 of 6 cases and a single case of infected epidural hematoma. Hill et al and Mukherjee et al also reported comparable reoperation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Both manufacturers produce implants on the basis of individual CT data sets and a virtual computer-aided design construction process. 6,24 A randomized multicenter study was favored in order to gain data from a higher number of patients in a shorter time period.…”
mentioning
confidence: 99%
“…However, as titanium does not biologically interact with natural bone, tissue regeneration and prosthesis integration are not possible. Moreover, in the case of using titanium plates, common consequences are sensitivity to temperature or foreign body sensation, and psychological problems for the patient having to accept the implant for the rest of his/her life (Eufinger et al, 2006). Some studies have shown postoperative complications after titanium cranioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article, the authors (Eufinger et al, 2006) concluded that only a biodegradable biomaterial, capable of leading to new bone regeneration and complete defect healing can result in real improvement for the patients.…”
Section: Discussionmentioning
confidence: 99%